INTEGRATIVE THEMATIC LEARNING MODEL BASED ON MULTICULTURAL VALUES AT TAMAN HARAPAN PRIMARY SCHOOL, MALANG CITY - Mustafida, Fita; Gafur, Abd. (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
The development of attitudes of intolerance and antipathy due to differences in religion, culture, language, and ethnicity is a common problem faced by plural societies, including Indonesia. Education that upholds the values of diversity, justice, and equality is the required educational model. Multicultural education through the values contained therein becomes the main material to be internalized by students as a systemic effort in school education to educate the value of cultural diversity amidst the erosion of values of respect for diversity in society. This study discusses an overview of an integrative thematic learning model based on multicultural values at Taman Harapan Elementary School, Malang City. Qualitative research approach with case study type. Data collection techniques use participant observation; in-depth interviews and also documentation as support. Data analysis through stages of condensation, data presentation, and concluding/verification according to the Milles-Huberman model. Based on this process, the results of this research show that the integrative thematic learning model based on multicultural values at Taman Harapan Elementary School is built from 1) Input that requires multicultural values; starting from students, teachers, curriculum, and infrastructure used. Inp management This ut is a manifestation of the institution's commitment to providing multicultural education. 2) The learning process is based on multicultural values including; planning, and implementation with various strategies, methods, media, and learning materials that contain multicultural values, and authentic assessment. As well as habituation to multicultural social interactions; and an academic atmosphere that respects cultural diversity. 3) Output learning outcomes that can shape students' multicultural knowledge, attitudes, and skills.